Effect of Low-Level Laser Therapy on the Osseointegration of Immediately Loaded Implants with a Connective Tissue Graft: A Randomized Clinical Trial: Effect of low-level laser therapy on the stability of implants - Momeni , Mohadese; Safari, Malihe; Sarrafzadeh, Arash; Momeni, Ehsan (Journal of Lasers in Medical Sciences, 2024)
Introduction: This study assessed the effect of low-level laser therapy (LLLT) on the osseointegration of immediately loaded implants with a connective tissue graft (CTG). Methods: This clinical trial was conducted on patients with buccal bone dehiscence requiring dental implants. A CTG was harvested from the palate and placed in the labial side by considering the 2 mm distance between the implant thread and bone. Autogenous bone was harvested from the tuberosity, mixed with the allograft, and implanted at the site. After sufficient torquing of the implant, a customized abutment was fabricated and placed. The patients were randomly assigned to two groups (n=5) of intervention and control. The patients in the intervention group received LLLT with a 940 nm gallium-aluminum-arsenide laser while those in the control group received placebo irradiation. The primary implant stability was measured before the delivery of customized abutment while the secondary implant stability was measured after 12 weeks by Osstell® and reported as the implant stability quotient (ISQ). Results: No significant difference was found in secondary ISQ between the laser and control groups (P>0.05). In the intervention group, an important difference was found between the primary and secondary ISQ in the buccolingual dimension (P<0.05) but not in the mesiodistal dimension (P>0.05). The two groups had no significant difference in gingival thickness or vertical bone gain (P>0.05). All implants were successful with no complications. Conclusion: LLLT had a significant positive efficacy for the enhancement of secondary stability of implants in the buccolingual dimension. CTG showed optimal efficacy for the treatment of buccal bone dehiscence.